Retrospective Cohort Study Comparing Infliximab-dyyb and Infliximab in Biologic-Naive Patients With Inflammatory Bowel Disease in the United States. Issue 3 (29th July 2021) - Smith, Joshua T; Velayos, Fernando S; Niu, Fang; Liu, Vincent; Delate, Thomas; Pola, Suresh; Le, Kim; Hui, Rita L
Abstract: Background: Real-world assessments of biosimilars are needed to understand their effectiveness and safety in practice settings that may differ from those seen in clinical trials or healthcare systems in different countries. To assess the effectiveness and safety of a biosimilar (infliximab-dyyb) and its reference product (infliximab) in patients with inflammatory bowel disease (IBD) in the United States. Methods: We conducted a retrospective cohort study of biologic-naive patients with IBD who started treatment with infliximab-dyyb or infliximab. The study included 3206 patients identified through electronic health records in a US integrated healthcare delivery system. The effectiveness outcome was a composite of IBD-related surgery, IBD-related emergency room visit, and IBD-related hospitalization within 12 months of initiation. Safety outcomes included incidence of any or serious infection, cancer, acute liver dysfunction, and tuberculosis. We used a non-inferiority test with an upper-limit margin of 10% to analyze effectiveness. Doubly robust methods incorporating Cox proportional hazard regression with standardized inverse probability of treatment weighting were used to analyze both effectiveness and safety outcomes. Results: The composite effectiveness outcome occurred in 107 of 870 patients (12.3%) in the infliximab-dyyb and 379 of 2336 patients (16.2%) in the infliximab groups. Infliximab-dyyb was non-inferior ( P < .01) and was not different (hazard ratio [HR] 0.81; confidence interval [CI] 0.65–1.01; P = .06) to infliximab. Safety outcomes were not different between infliximab-dyyb and infliximab for any infections (HR 1.01; CI 0.86–1.17; P = .95), serious infections (HR 0.83; CI 0.54–1.26; P = .38), cancers (HR 0.83; CI 0.44–1.54; P = .55), and tuberculosis (HR 0.59; CI 0.10–3.55; P = .57). Conclusions: Initiation of infliximab-dyyb was non-inferior to infliximab among biologic-naive patients with IBD in an US integrated healthcare delivery system. Lay Summary: In this US-based, retrospective, multicenter, cohort study of 3206 biologic-naive patients with inflammatory bowel disease (IBD), treatment with the biosimilar infliximab-dyyb was non-inferior to reference product infliximab for the effectiveness composite of IBD-related surgery, IBD-related emergency room visit, and IBD-related hospitalization. Graphical Abstract: